Factors associated with family adherence to tuberculosis preventive therapy based on the health belief model: A systematic review - Gutteres, Domingos; Luthfa, Iskim; Setyowati, Wahyu Endang (Lentera Perawat, 2026)
Background: Family adherence to tuberculosis preventive therapy (TPT) plays an important role in preventing tuberculosis transmission and progression among household contacts. The Health Belief Model (HBM) provides a useful framework for explaining how families perceive risk, severity, benefits, and barriers related to preventive therapy. However, evidence on factors associated with family adherence to TPT based on the HBM remains scattered across studies and has not been synthesized comprehensively. Objective: This systematic review aimed to identify and synthesize factors associated with family adherence to tuberculosis preventive therapy based on the constructs of the Health Belief Model. Methods: This study used a systematic review design. Literature searches were conducted in Google Scholar, PubMed, ProQuest, and ScienceDirect for articles published between 2019 and 2025 in English or Indonesian. The review included empirical studies that examined family-related adherence to tuberculosis treatment or preventive therapy and studies that used or reflected HBM constructs. Data were extracted using a structured form and synthesized narratively according to HBM domains and family-related adherence factors. Results: Eight studies were included in the final synthesis. The findings showed that family support consistently influenced adherence behavior in tuberculosis treatment and preventive therapy. Perceived benefits emerged as the strongest predictor of TPT acceptance, while perceived susceptibility, perceived severity, perceived barriers, and self-efficacy were also significantly associated with adherence-related behavior. Knowledge and attitudes contributed to treatment adherence, and HBM-based educational interventions improved medication adherence, nutritional practices, and transmission prevention behavior. Conclusion: Family adherence to tuberculosis preventive therapy is a multidimensional behavioral outcome influenced by family support, HBM-related perceptions, knowledge, attitudes, and contextual barriers. The Health Belief Model provides a relevant theoretical basis for understanding and strengthening adherence in family and household contexts.